The Potential for Gold Mineralisation in the Greenstone Belt of Busia District, South Eastern Uganda - Mbonimpa, A. B.; Barifaijo, E.; Tiberindwa, J. V. (African Journal of Science and Technology, 2007)
Busia district in south eastern Uganda is one of the areas in the country with a history of potential for gold mineralisation and exploitation. Gold was first discovered in the Archaean greenstone belt of Busia by Davies in 1932. Only small mining operations, mostly artisan in character, have taken place in the district since then except the newly opened mines by Busitema Mining Company. However, all recent work in the area indicates potential for gold exploitation. Both quartz vein-hosted and Banded Iron Formation (BIF)-hosted gold deposits occur in Busia district. The results of Electron Microprobe (EMP) analysis of 10 rock samples from the quartz vein deposits and AAS analysis of 10 rock, 27 soil and 18 stream sediment samples taken from Busia district are presented in this work.Gold occurs as electrum or native gold inclusions in pyrite with fineness in the range of 451 – 863; and as invisible gold in sulphide minerals (up to 5700 ppm in pyrite). The main ore minerals are pyrite, magnetite, ilmenite, galena, pyrrhotite, chalcopyrite, covellite and rutile. Gold values of the stream sediment samples average 7.7 ppm Au, the highest being 38.6 ppm Au. Soil sampling was done in the three areas proposed for follow-up by Mroz et al. (1991), of which the Tira area has the first priority soil anomaly (up to 4.8 ppm Au) followed by the Osapiri area (up to 2.8 ppm Au). There is a strong correlation between the distribution of lead and that of gold.
Keywords: Busia district, Archaean greenstone belt, quartz vein-hosted gold deposits, banded iron formation-hosted deposits, sulphides